Heterotetranuclear Complexes of Reduced and Non‐reduced Bridging 1, 2, 4, 5‐Tetrazine Ligands with 1, 1′‐Bis(diphenylphosphanyl)‐ferrocene‐copper(I)12. Issue 2 (30th January 2015) - Bach, Monika; Roy, Sayak; Sarkar, Biprajit; Bubrin, Martina; Niemeyer, Mark; Fiedler, Jan; Duboc, Carole; Kaim, Wolfgang
Abstract The complexes (μ‐bptz)[Cu(dppf)]2(BF4)2 [(1)(BF4)2] [bptz = 3, 6‐bis(2‐pyridyl)‐1, 2, 4, 5‐tetrazine, dppf = 1, 1′‐bis(diphenylphosphanyl)ferrocene] and (μ‐bpztz)[Cu(dppf)]2(PF6)2 [(2)(PF6)2] [bpztz = 3, 6‐bis(2‐pyrazinyl)‐1, 2, 4, 5‐tetrazine] contain two redox‐active heterodinuclear FeIICuI moieties, bridged by a redox‐active ligand. A crystal structure determination of (1)(BF4)2·2CH2Cl2 confirms the non‐reduced aromatic nature of the bridge, in contrast to previous results on dicopper(I) complexes of bptz. Facile one‐electron reduction produces the radical complexes (μ‐bptz)[Cu(dppf)]2+ (1+) and (μ‐bpztz)[Cu(dppf)]2+ (2+), which could be isolated [as (1)(BF4)] and studied by variable frequency EPR to provide hyperfine (9.5 GHz) and g anisotropy information (285 GHz). Cyclic voltammetry and UV/Vis/NIR spectroelectrochemistry indicate a reversible two‐electron oxidation of the well separated (ca. 13.4 Å) ferrocene termini.